2014
DOI: 10.1007/s11033-014-3254-y
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in the association of the glutathione S-transferase T1 (GSTT1) null genotype and risk of gastric carcinoma: a systematic review and meta-analysis

Abstract: We performed a systematic review and meta-analysis of the association between the glutathione S-transferase T1 (GSTT1) deletion polymorphism and gastric cancer risk in populations from different ethnic backgrounds, based on a comprehensive literature search of the MEDLINE, EMBASE, and COCHRANE libraries. Thirty-six individual case-control studies comprising 7,689 gastric cancer cases and 12,445 controls were included in our meta-analysis. Overall, the GSTT1 null genotype appeared to increase gastric cancer ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Marked association of GSTT1 deletion with lung cancer [38] and gastric cancer [39] has Interestingly, our subgroup analysis by ethnicity showed that the GSTT1 polymorphism played different roles in Asian and Caucasian populations. In the Asian population, GSTT1 null genotype was significantly associated with increased endometriosis risk, whereas in Caucasians, no significant correlation has been observed.…”
Section: Commentsmentioning
confidence: 72%
“…Marked association of GSTT1 deletion with lung cancer [38] and gastric cancer [39] has Interestingly, our subgroup analysis by ethnicity showed that the GSTT1 polymorphism played different roles in Asian and Caucasian populations. In the Asian population, GSTT1 null genotype was significantly associated with increased endometriosis risk, whereas in Caucasians, no significant correlation has been observed.…”
Section: Commentsmentioning
confidence: 72%
“…Over recent years, genome-wide association studies (GWAS) have identified multiple genetic loci associated with gastric cancer risk 23 - 25 . In addition, much effort in case-control studies has been spent in searching for cancer susceptibility genes, such as genes coding for inflammatory mediators 7 , DNA repair 26 , apoptosis 27 and carcinogen metabolism 28 . In a Nature Immunology article, Rutkowski and his colleges reviewed that complement proteins might facilitate the process of carcinogenesis by increasing activity of mitogenic signaling pathways, inducing cellular proliferation, and promoting immunosupression 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Of the plethora of articles retrieved from the second MEDLINE search, we identi fied 28 systematic reviews of animal stud ies, [3941] GSHrelated genetic polymorphisms linked to various cancers (colo rectal can cer, [42] leukaemia, [43,44] lung cancer, [45,46] blad der can cer, [47] gastric cancer, [48,49] prostate cancer, [5053] adult brain tumours, [54] basal cell carcinoma [55] ) and linked to other disorders (autism, [12,13] hyper tension, [56,57] respiratory diseases, [58,59] cataract, [60] myelo dysplastic syndrome, [61,62] glioma [63] and male idio pathic infertility. [64] ) There were 9 RCTs identified from two systematic reviews of the use of GSH to reduce chemotherapy induced toxicity (6 cisplatin, 2 axaliplatin, 1 platinum); most suggested less toxicity in GSH groups.…”
Section: Clinical Updatementioning
confidence: 99%